Control de inventario de la ferretería automotriz el maestro del cantón Baba. - Franco Burgos, Mallerly Marilin (2022)
The present case study deals with inventory control in the hardware store automatize the teacher of the canton Baba. The main objective that seeks to determine the quality of inventory control that is applied in the automotive hardware store, the master of the Baba canton. For an efficient development, the quantitative method was used, with the purpose of obtaining information on the inventory control process in the The master automotive hardware store was used as an information gathering technique, the survey, in this case it allows the person in charge of the investigation to find a solution to a present problem. To conclude the management of inventories has reached the summit of the problems of the administration in the automotive hardware store, the teacher, based on the information obtained, through the application of the survey, it is determined that, since there is no correct management Regarding inventory control, this causes loss of money and time, having a low level of customer service, by not having what the consumer requests, causing a decrease in cash flow for the company. Finally, it is recommended to carry out periodic control of the merchandise that is offered in the automotive hardware store el maestro. Apply inventory control methods to prevent problems arising from excess or insufficient supply of products in the hardware store and meet the requirements established by customers, satisfying their needs and not opting to move to the competition.